2004
DOI: 10.1002/ana.20049
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CCR7 in multiple sclerosis: Implications for CNS immunity

Abstract: It is unclear how immune cells traffic between the lymphoid compartment and the central nervous system (CNS), which lacks lymphatic vessels and is shielded by the blood-brain barrier. We studied the expression of CCR7, a chemokine receptor required for migration of T cells and dendritic cells (DCs) to lymphoid organs, in the CNS of patients with multiple sclerosis (MS) to gain insight into pathways for CNS immune cell trafficking. Inflamed MS lesions contained numerous CCR7+ myeloid cells expressing major hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
175
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(192 citation statements)
references
References 51 publications
11
175
1
5
Order By: Relevance
“…Our discovery that CCR7 ϩ CSF lymphoblasts have slightly increased Kv1.3 channels on their membrane, but are primed to rapidly become Kv1.3 high T EM has important implications in understanding CNS recruitment. These data are consistent with a recent report by another group (30) in which CSF cells were CCR7 ؉ but parenchymal cells were CCR7 Ϫ . We considered the possibility that CCR7 expression might reflect their activation state because we and others have reported that CCR7 is transiently up-regulated on T helper 1 cells during early activation (20,31).…”
Section: Discussionsupporting
confidence: 93%
“…Our discovery that CCR7 ϩ CSF lymphoblasts have slightly increased Kv1.3 channels on their membrane, but are primed to rapidly become Kv1.3 high T EM has important implications in understanding CNS recruitment. These data are consistent with a recent report by another group (30) in which CSF cells were CCR7 ؉ but parenchymal cells were CCR7 Ϫ . We considered the possibility that CCR7 expression might reflect their activation state because we and others have reported that CCR7 is transiently up-regulated on T helper 1 cells during early activation (20,31).…”
Section: Discussionsupporting
confidence: 93%
“…Instead CCR7 predominantly stained parenchymal cells with a morphology resembling activated microglia in NLGM and NLWM (Fig. 1F, insert) as described previously for MS plaques (Kivisakk et al, 2004).…”
Section: Inflammatory Infiltrates In Nlgmsupporting
confidence: 81%
“…Since anti-inflammatory macrophages express the lymph node homing receptor CCR7 [50], we determined whether a CCR7-dependent mechanism could be involved. This study shows that, similar to APC in MS brain as well as MOG-containing cells in EAEaffected rhesus CLN [21,51], myelin-containing cells in human MS CLN and in vitro express CCR7, but MAP-2-containing cells do not. CLN from EAE-affected CCR7-deficient mice contain slightly more myelin and neuronal antigens as compared to CLN from EAE-affected wild-type mice, indicating that CCR7 is not necessarily involved.…”
Section: Discussionmentioning
confidence: 53%